Hello Swift! : iOS app programming for kids and other beginners - Bakshi, Tanmay (Manning Publications Co., 2019)
"Hello Swift! is a how-to guide to programming iOS Apps with the Swift language, written from a kid's perspective. This approachable, well-illustrated, step-by-step guide takes you from beginning programming concepts all the way through developing complete apps. (Adults will like it too!)"--Amazon,